The Spanish-Ottoman conflict over Tunisia 941-982 AH /1534-1574 AD - Youssef , Elham; Saker , Walaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research deals with the nature of the Spanish-Ottoman conflict on the strategic Tunisia, whose two sides exchanged its occupation more than once,As a result of weakness of the Hafsid state and inabilitly to protect the country and to confront foreign ambitions and its use in Spain, it was natural that the Ottoman state to annex Tunisia to its property,which was not accepted by the Spanish Emperor Charlecan , Which led to the entry into the Spanish conflict can be identified by studying the causes, and follow the stages demonstrated by the occupation of Khairuddin Barbaross to Tunisia /9411534, and then the campaign of Charlecan 942/1535, and the battle of Lepanto 979 / 1571, which turned Tunisia into a semi-colony of Spain, ending this conflict in /9821574 by attaching Tunisia to the Ottoman Empire and ending the rule of Hafs and weakening the Spaniards and their status in the region.